2021
DOI: 10.1021/acssynbio.1c00360
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Colorimetric Reporter Enzymes in the PURE System

Abstract: Colorimetric reporter enzymes are useful for generating eye-readable biosensor readouts that do not require a device to interpret, an attractive property for applications in remote or developing parts of the world. The use of cell-free gene expression further facilitates such applications via amenability to lyophilization and incorporation into materials like paper. Currently, detection of multiple analytes simultaneously with these systems requires multiple reactions or a device. Here we evaluate seven enzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…Similar to Sharpes's finding of incompatibility between some enzyme−substrate systems when mixed together, we also find that our NcoI system was not functional in the presence of the two other reporters when all were coexpressed in the same reaction. 13 We note that when the NcoI system was expressed by itself in the reaction mix individually, it did work albeit far more slowly. Further analysis is required to clearly understand the reason for NcoI reporter's inefficacy, but we speculate possible incompatibility between QD 625 (due to its large surface area) and some PURExpress enzyme(s)'s coordination on the QD surface or our use of a sub-optimized NcoI gene sequence, whereas the commercially obtained pure enzyme may in actuality be a vastly improved mutationally selected version that is proprietary.…”
Section: ■ Conclusionmentioning
confidence: 94%
See 3 more Smart Citations
“…Similar to Sharpes's finding of incompatibility between some enzyme−substrate systems when mixed together, we also find that our NcoI system was not functional in the presence of the two other reporters when all were coexpressed in the same reaction. 13 We note that when the NcoI system was expressed by itself in the reaction mix individually, it did work albeit far more slowly. Further analysis is required to clearly understand the reason for NcoI reporter's inefficacy, but we speculate possible incompatibility between QD 625 (due to its large surface area) and some PURExpress enzyme(s)'s coordination on the QD surface or our use of a sub-optimized NcoI gene sequence, whereas the commercially obtained pure enzyme may in actuality be a vastly improved mutationally selected version that is proprietary.…”
Section: ■ Conclusionmentioning
confidence: 94%
“…In a similarly focused study, Sharpes et al identified seven candidate colorimetric reporter enzymes from the literature with each enzyme having one to three substrates that were all commercially available for screening in cell-free assays as output signals. 13 After intensive screening of several different combinations, they showed that at least one pair of these reporter/substrate combinations can produce four distinct colors from two enzymes, suggesting utility for multiplexing of sensors in a single reaction. In this report, we focused on developing multiplexed optical outputs from reporter enzymes expressed as part of biosensing in cell-free reactions.…”
Section: ■ Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cell-free biosensors that can operate free of any device are also attractive for applications where factors such as weight and portability are especially important. One such example of this is the utilization of the PURE system towards biosensing, which demonstrated compatibility with colorimetric reporter enzymes that would allow simple visual detection of multiple target analytes [63]. Technological innovations in the integration of cell-free systems demonstrate the advantage they present for the biosensing of target analytes, especially those that are toxic or present challenges for cell-based systems.…”
Section: Cell-free Biosensingmentioning
confidence: 99%